ChemInform Abstract: Structure, Properties, and Disorder in the New Distorted‐Hollandite PbIr4Se8. Issue 45 (October 2016) - Trump, Benjamin A.; McQueen, Tyrel M.
Abstract: The polycrystalline title compound is prepared by annealing the elements in a ratio corresponding to (PbSe)1.1 (IrSe2 )2 (Ar filled silica tubes, 1.